Mechanofluorescent Polymer Brush Surfaces that Spatially Resolve Surface Solvation - Besford, Quinn A.; Merlitz, Holger; Schubotz, Simon; Yong, Huaisong; Chae, Soosang; Schnepf, Max J.; Weiss, Alessia C. G.; Auernhammer, Guenter K.; Sommer, Jens-Uwe; Uhlmann, Petra; Fery, Andreas (ACS nano, 2022)
Polymer brushes, consisting of densely end-tethered polymers to a surface, can exhibit rapid and sharp conformational transitions due to specific stimuli, which offer intriguing possibilities for surface-based sensing of the stimuli. The key toward unlocking these possibilities is the development of methods to readily transduce signals from polymer conformational changes. Herein, we report on single-fluorophore integrated ultrathin (<40 nm) polymer brush surfaces that exhibit changing fluorescence properties based on polymer conformation. The basis of our methods is the change in occupied volume as the polymer brush undergoes a collapse transition, which enhances the effective concentration and aggregation of the integrated fluorophores, leading to a self-quenching of the fluorophores’ fluorescence and thereby reduced fluorescence lifetimes. By using fluorescence lifetime imaging microscopy, we reveal spatial details on polymer brush conformational transitions across complex interfaces, including at the air-water-solid interface and at the interface of immiscible liquids that solvate the surface. Furthermore, our method identifies the swelling of polymer brushes from outside of a direct droplet (i.e., the polymer phase with vapor above), which is controlled by humidity. These solvation-sensitive surfaces offer a strong potential for surface-based sensing of stimuli-induced phase transitions of polymer brushes with spatially resolved output in high resolution.
CRIS-Team Scopus Importer:2022-04-14
Keywords: co-nonsolvency effects; droplet wetting; fluorescence lifetime imaging microscopy; mechanofluorescence; poly(N-isopropylacrylamide); polymer brushes